2022
DOI: 10.3390/membranes12010065
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of ECTFE Porous Membrane for Dehumidification of Gaseous Streams through Membrane Condenser

Abstract: Due to the good hydrophobicity and chemical resistance of poly(ethylene trifluoroethylene) (ECTFE), it has been an attractive potential material for microfiltration, membrane distillation and more. However, few porous hydrophobic ECTFE membranes were prepared by thermally induced phase separation (TIPS) for membrane condenser applications. In this work, the diluent, di-n-octyl phthalate (DnOP), was selected to prepare the dope solutions. The calculated Hassen solubility parameter indicated that ECTFE has good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
8
1
Order By: Relevance
“…The loss of hydrophobicity and the concomitant decrease in the contact angle of the membrane progresses with the time of operation [ 32 ]. The accumulation of foulants on the membrane surface, and in the membrane pores is a time-dependent process and is the main factor for hydrophobicity degradation [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The loss of hydrophobicity and the concomitant decrease in the contact angle of the membrane progresses with the time of operation [ 32 ]. The accumulation of foulants on the membrane surface, and in the membrane pores is a time-dependent process and is the main factor for hydrophobicity degradation [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ECTFE membranes prepared at 20% TOTM showed high recovery performance during the MC process, achieving condensation flux of 1.71 kg•m −2 •h −1 and water recovery rate of 54.84%, better than commercial hydrophobic PVDF membranes, demonstrating the potential of ECTFE membranes in the MC process. Meanwhile, compared to the previous work of the group [28], this study further changes the membrane preparation method to improve the water recovery rate.…”
Section: Performancementioning
confidence: 96%
“…The Ozawa model [45] is based on Evans' theory, and treats NIT crystallization as the sum of infinitesimal isothermal crystallization processes. Considering the nucleation and crystal growth, the Avrami equation can be modified to obtain Equation (15), as follows:…”
Section: Non-isothermal Crystallization Kinetics Based On Ozawa Modelmentioning
confidence: 99%
“…As a result, a lot of salt might deposit on membrane surface to realize seawater desalination. Pan et al [15] fabricated ECTFE-SiO 2 hybrid porous membrane with hierarchical micro/nano-structural suface via thermally induced phase separation (TIPs). The results showed that the membrane had high oil/water separation efficiency, and can also be reused many times in various PHs.…”
Section: Introductionmentioning
confidence: 99%